2011
DOI: 10.1097/jto.0b013e3181fa646a
|View full text |Cite
|
Sign up to set email alerts
|

Terameprocol (Tetra-O-Methyl Nordihydroguaiaretic Acid), an Inhibitor of Sp1-Mediated Survivin Transcription, Induces Radiosensitization in Non-small Cell Lung Carcinoma

Abstract: Introduction Survivin, an inhibitor of apoptosis protein (IAP) and key regulator of mitosis, is up-regulated in a variety of cancers and is often associated with a worse prognosis. Terameprocol down-regulates the Sp1-mediated transcription of survivin and Cdk1, which is important for cell cycle progression, as well as many other proteins. Survivin inhibition has previously been shown to result in the induction of apoptosis and radiosensitization. Methods This study examined the effects of terameprocol admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 36 publications
(42 reference statements)
0
24
0
Order By: Relevance
“…The pro-survival protein survivin is an apoptosis inhibitor and a key regulator of mitosis, closely associated with carcinogenesis (44). Consistent with its role, it was demonstrated to be upregulated in many human cancer cells (45). Therefore, cyclin D1, survivin and Mcl-1 in cancer cells have emerged as potential therapeutic targets.…”
Section: Discussionmentioning
confidence: 88%
“…The pro-survival protein survivin is an apoptosis inhibitor and a key regulator of mitosis, closely associated with carcinogenesis (44). Consistent with its role, it was demonstrated to be upregulated in many human cancer cells (45). Therefore, cyclin D1, survivin and Mcl-1 in cancer cells have emerged as potential therapeutic targets.…”
Section: Discussionmentioning
confidence: 88%
“…NDGA also inhibits cyclooxygenase (COX), formyltetrahydrofolate synthetase, and carboxylesterase to a lesser extent. However, a recent study showed that although terameprocol decreases survivin transcription and protein expression, this did not correlate with an increase in apoptosis (Sun et al, 2011). 5.3).…”
Section: Terameprocolmentioning
confidence: 95%
“…TMP is a semi-synthetic small molecule that disrupts the interaction between Sp1 and guanine-cytosinerich motifs, thereby inhibiting Sp1 transcriptional activity. 8,[18][19][20] We have observed the inhibition of Sp1 binding to known Sp1-responsive promoters by TMP using chromatin immunoprecipitation assay, and decreased expression levels of Sp1-regulated proteins, confirming that the antitumor activity of TMP in WM occurs via selective targeting of Sp1 activity.…”
Section: Discussionmentioning
confidence: 84%